1611 The Comorbidity of Chronic Pain and Insomnia in a Community Adolescent Sample: Prevalence and Association with Sociodemographic and Psychosocial Factors. (October 2012) - Wong, WS; Siu, N; Wong, C
Abstract : Background and Aims: The comorbidity of chronic pain and insomnia has received increasing research attention in Western clinical pediatric populations; yet, little is known about its sociodemographic and psychological correlates in non-Western community pediatric populations. This study aimed to examine the prevalence of comorbid chronic pain and insomnia and its associated factors in a community sample of Chinese adolescents. Methods: A total of 1, 518 adolescents aged from 11–19 years participated in this school-based study. Apart from sociodemographic background, participants were assessed on chronic pain, insomnia, depression, perceived stress, and social support. Prevalence of co-occurrence of chronic pain and insomnia was determined. Subjects with single symptom were compared with those with symptom co-occurrence on pain characteristics and sleep patterns. Multiple regression model evaluated factors associated with symptom comorbidity. Results: The prevalence of comorbid chronic pain and insomnia was 19.1% (95% CI: 16.9, 21.4). Fully adjusted stepwise regression analyses identified being female, more depressive symptoms, and higher perceived stress to be significantly associated with comorbid symptoms. Adolescents with both symptoms reported significantly more pain sites, higher worst pain, and higher pain-associated interference than those reported chronic pain only. Subjects with comorbid symptoms also had poorer subjective sleep quality, greater sleep disturbances, and more daytime dysfunction than those reported insomnia only. Conclusions: Our data offered preliminary evidence that comorbid chronic pain and insomnia occurred among about one-fifth in the present sample of Chinese community adolescents.